2017
DOI: 10.1210/en.2017-00288
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Effects of Bile Acids on Glucose Metabolism and Insulin Sensitivity in a Male Mouse Model of Prenatal Undernutrition

Abstract: Prenatal undernutrition and low birth weight are associated with risk of type 2 diabetes and obesity. Prenatal caloric restriction results in low birth weight, glucose intolerance, obesity, and reduced plasma bile acids (BAs) in offspring mice. Because BAs can regulate systemic metabolism and glucose homeostasis, we hypothesized that BA supplementation could prevent diet-induced obesity and glucose intolerance in this model of developmental programming. Pregnant dams were food restricted by 50% from gestationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…In this study, FXR acted as a transcription factor for BA synthetic enzymes and transporter proteins, thereby maintaining homeostasis through BA synthesis, influx, and efflux (Mueller et al, 2015 ). Consistent with our observations, Ma et al ( 2017 ) reported that UDCA supplementation increased CYP7B1 mRNA levels and improved fasting glucose levels and hepatic steatosis in a diet-induced NAFLD model mouse. Our study showed that UDCA administration in mice enhanced CYP7B1 expression but reduced CYP8B1 expression, leading to an elevated non-12-OH/12-OH BA ratio and a decrease in diet-induced obesity.…”
Section: Activation Of the Ba Alternative Pathway Results In The Improvement Of Metabolismsupporting
confidence: 93%
“…In this study, FXR acted as a transcription factor for BA synthetic enzymes and transporter proteins, thereby maintaining homeostasis through BA synthesis, influx, and efflux (Mueller et al, 2015 ). Consistent with our observations, Ma et al ( 2017 ) reported that UDCA supplementation increased CYP7B1 mRNA levels and improved fasting glucose levels and hepatic steatosis in a diet-induced NAFLD model mouse. Our study showed that UDCA administration in mice enhanced CYP7B1 expression but reduced CYP8B1 expression, leading to an elevated non-12-OH/12-OH BA ratio and a decrease in diet-induced obesity.…”
Section: Activation Of the Ba Alternative Pathway Results In The Improvement Of Metabolismsupporting
confidence: 93%
“…Barker et al [ 15 ] firstly proposed the “thrifty phenotype” hypothesis, stating that the fetal under-nutrition can compel the body to store fat (after improvement of the nutritional environment) rather than muscle. This adaptive adjustment in the fetus is more likely to lead to obesity, IR, and type 2 diabetes [ 7 ]. Our study found that in the LBW mice with a high-fat diet, glucose regulation was more seriously disrupted in adulthood and IR was more evident, which were consistent with the findings of previous studies [ 6 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ye et al observed that catch-up growth in early childhood and disorders involving in glucose and lipid metabolism in adulthood were accompanied by impaired IGFBP3/IGF-1/IRS-1/Akt signaling pathway in the liver [ 6 ]. In the early stage of our study, we found that deoxycholic acid and cholic acid levels in the blood of LBW mice were significantly lower than those of normal birth weight mice, suggesting that cholic acid metabolism might play a role in adult type 2 diabetes mellitus caused by LBW [ 7 ]. However, the mechanisms inducing IR and the development of diabetes in LBW individuals remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown strong causative relation between restricted intrauterine growth and adult metabolic reprograming in rodents ( 17 , 18 ). To reduce the potential impact of uneven intrauterine nutrition accompanied by different litter size, we used a previously developed ICR mouse model ( 19 ). Adult (6- to 8-week-old) male and female ICR mice were purchased from Beijing Vital River Laboratory Animal Technology Co., Ltd. and caged.…”
Section: Methodsmentioning
confidence: 99%